The leaf-miner flies (Diptera: Agromyzidae) of Costa Rican cloud forests - Boucher, Stéphanie; Borkent, Art; Brown, Brian V. (Zootaxa, 2025)
Cloud forests are known as important reservoirs of biodiversity and species endemism, but they are also one of the most threatened of tropical ecosystems. This study investigates the leaf-miner flies (Diptera: Agromyzidae) collected over a period of one year at three different cloud forest localities in Costa Rica, as part of the Zurquí All Diptera Biodiversity Inventory (ZADBI). A total of 976 specimens of Agromyzidae was collected, resulting in the identification of 158 species (or morphospecies). This number is surprisingly high, considering that only 65 species of Agromyzidae were previously recorded in Costa Rica. Most of the species were collected from the main site (Zurquí de Moravia) and only six species were collected at all three sites. Most of the species were collected from a Malaise trap set-up near a forest-edge at the main site, but the more limited sampling at the other two sites added some unique species and one unrecorded genus (Haplopeodes Steyskal) for Costa Rica. Of the 14 previously recorded Neotropical genera of Agromyzidae, 12 were sampled at the cloud forest sites, in addition to the genus Metopomyza Enderlein, previously unreported from the Neotropical Region. The 26 species of the genus Phytoliriomyza Hendel are noteworthy as only 28 congeneric species were previously reported for the entire Neotropical Region. We also discuss the presence of two predominantly northern temperate genera, Phytomyza and Metopomyza, at these sites. Additionally, taxonomic discussion and geographical distributions are provided for the following species: Agromyza fusca Spencer, Calycomyza dominicensis Spencer, Calycomyza meridiana (Hendel), Japanagromyza sasakawai Monteiro, Carvalho-Filho & Esposito, Liriomyza archboldi Frost, Melanagromyza wedeliae Spencer. Finally, we provide comments and a few illustrations for a selection of newly identified species (Cerodontha (Dizygomyza) n.sp.; Liriomyza n.sp.; Haplopeodes ZADBI-1; Cerodontha (Cerodontha) ZADBI-8; Metopomyza ZADBI-4, Phytomyza ZADBI-3). The high species richness and the discovery of several potentially endemic species, support the importance of conservation efforts of these fragile ecosystems.